Кримінально-правове значення суспільної небезпеки - Рудковська, М.; Rudkovs’ka, М. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Проведено аналіз кримінально-правового значення суспільної небезпеки у сфері суспільно-правової свідомості, нормотворення та правозастосування. Автор вважає, що суспільна небезпека не властива адміністративним правопорушенням. Відповідно, суспільно небезпечними є лише злочини. Ступінь суспільної небезпеки являє собою умову, що робить злочин більш або менш суспільно небезпечним. За висновком автора є дві підстави кримінальної відповідальності, які виступають в єдності: перша матеріальна підстава– суспільно небезпечне діяння як факт об’єктивної реальності і друга юридична підстава– діяння, що містить ознаки складу злочину, вказані в кримінально-правовій нормі. Суспільна небезпека покладена в основу класифікації злочинів за ступенем тяжкості, яка відображена у ст. 12 КК України, де ступінь тяжкості виступає як показник типового рівня суспільної небезпеки злочинів, що відображено через санкції кримінально-правових норм. For the purpose of comprehensive analysis of public danger as a sign of a crime, the author has investigated its criminal-legal estimation in the social and legal consciousness, rule-making procedures and application of the law. Particular attention is paid to clarifying the following questions: whether public danger is characteristic and applicable only to the crimes or some other offenses too, for instance, antisocial offenses, which are governed by the norms of morality; whether public danger is the autonomous basis for criminal responsibility, one of the two, along with the offense itself or it is not a ground for criminal responsibility in general; the impact of public danger on realizationof such principles as justice, equality, legality,as well as humanism and guilt. In addition, the article discusses the notion public danger as the basis for the criminalization and decriminalization of criminal actions and as a basis for the classification of offenses in accordance with a degree of severity, where severity index serves as a model of public danger of the crime, which is reflected in the sanctions of the criminal-legal norms. The degree of severity is also considered to be an index of individual public danger, which is taken into account in the context of the individualization of criminal responsibility. Thus, on the one hand, thetypical severity of the crime is the most powerfultool for differentiation of criminal responsibility, but on the other – individual severity index represent individual level of public danger in every specific crime and is taken into account by the court at sentencing, release from criminal liability, release from punishment orimprisonment.
Criminal-legal Meaning of the Notion Public Danger
Keywords: злочин; суспільна небезпека; суспільна шкідливість; малозначне діяння; адміністративне правопорушення; склад злочину; crime; public danger; public harm; insignificant acts; administrative offense; offense